Research methods in consumer law : a handbook - Micklitz, Hans-Wolfgang, 1949-; Sibony, Anne-Lise; Esposito, Fabrizio (Handbooks of research methods in law, 2018)
European consumer law seeks to ensure that consumers receive sufficient information about goods and services, are not subject to unfair contract clauses or unfair commercial practices and have the means to redress grievances. This Handbook specifically considers the impacts of different disciplines and methods as it presents the state of the art in consumer law research and in particular offers intriguing new insights from behavioural science. Research Methods in Consumer Law shows how different lenses help to highlight under-researched areas of consumer law and engage with current debates in order to suggest pertinent legal reforms. Rules meant to protect consumers are often premised on the fact that small print is read, understood and acted upon. Acknowledging that this is rarely the case, the expert contributors offer new perspectives, informed by the study of how real people behave and paying careful attention to methodology. Offering the tools to engage in promising and socially useful legal research, this Handbook will appeal to students and scholars across the fields of law and behavioural science, as it offers a fresh look at the relation between EU consumer law and other disciplines oriented to solving practical problems.